Cross-linked Chitosan Synthesis Using Glutaraldehyde and Functional Group Identification as well as Its Deacetylation Degree - Bagus Rahmat Basuki; I Gusti Made Sanjaya (Jurnal ILMU DASAR, 2009)
Cross-linked chitosan with 78,12% deacetylation degree, synthesed from chitosan bead with 135,982% swelling degree were conducted. Chitosan bead has prepared from chitosan that was dissolved with watery acetic acid and coagulated with sodium hydroxide. Chitosan with 79,6% deacetylation degree was prepared from chitin that was submitted to a deacetylation reaction. Chitin were applied, isolated from giant tiger shrimp that was submitted to a demineral and deproteination reaction. Functional group of the cross-linked chitosan with glutaraldehyde were investigated by the Infra Red spectroscopy and deacetylation degree were investigated by the base line methods. Chitin, chitosan and chitosan bead have the same structure. The difference between chitin and chitosan was the deacetylation degree and chitosan bead in the physical shape. The deacetylation degree and swelling degree of chitosan bead was decreased by cross-linking process.